Hubungan Antara Asupan Vitamin A dan Seng dengan Penanda Inflamasi pada Pasien Tuberkulosis Paru di Rumah Sakit Umum Pusat Persahabatan - Mitrasari, Surya; Nurwidya, Fariz; Wulandari, Yohannessa; Agustin, Heidy (RSUP Dr. Kariadi, 2026)
BACKGROUND: Indonesia has the second highest burden of tuberculosis (TB) worldwide, with an incidence of 354 per 100,000 population and approximately 969,000 cases reported in 2021. Micronutrients such as vitamin A and zinc play important roles in immune function and may influence inflammatory responses in TB. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are potential markers of systemic inflammation; however, evidence regarding their association with dietary micronutrient intake in pulmonary TB patients remains limited, particularly in Indonesia. AIMS: To examine the association between vitamin A and zinc intake and inflammatory markers in pulmonary TB patients. METHODS: A cross-sectional study was conducted among 133 pulmonary TB patients recruited consecutively from March to April 2024 at Persahabatan Hospital. Vitamin A and zinc intake were assessed using a semi-quantitative food frequency questionnaire (SQ-FFQ), while NLR and PLR values were obtained from medical records. Data normality was tested using the Kolmogorov–Smirnov test, and correlations were analyzed using Spearman’s test. The median vitamin A intake was 105.47 RE/day and zinc intake was 7.38 mg/day, with median NLR and PLR of 2.91 and 202.08, respectively. RESULTS: No significant correlations were found between vitamin A or zinc intake and NLR or PLR (p > 0.05). CONCLUSION: In conclusion, vitamin A and zinc intake were not associated with inflammatory markers in pulmonary TB patients, although host-related factors may contribute to the inflammatory response.